Analisis Penerapan Rekam Medis Elektronik di Puskesmas X Kota Semarang dengan Metode Hot-Fit - Titi Santika; Faizatu Fithriah; Sofy Fara Yoha; Lilya Oktaviana Dewi; Edy Susena (Lembaga Pengembangan Kinerja Dosen, 2025)
X Health Center has implemented EMR on SIMPUS since 2009-2010. However, from the preliminary study, it was found that there were obstacles such as network trouble, long loading when many users were pulling data on the system, and there was no SOP for down time: The purpose of this study is to analyze the implementation of Electronic Medical Records at X Health Center, Semarang City in the aspects of Human, Organization, Technology, Net-benefit. Methods: This study used a descriptive qualitative approach with interviews, observations and documentation studies. Results: The results of research at X Health Center show that there are problems in implementing EMR at X Health Center, in the human aspect, namely system training is still given only to representative officers such as IT and SIK staff. In the organizational aspect, namely limited facilities and lack of manpower. On the technology aspect, namely internet network instability, inconsistent electricity supply and generator unpreparedness and hardware limitations. While in the net-benefit aspect, the implementation of EMR has an impact on increasing the efficiency and effectiveness of X Health Center services. Conclusion: The implementation of electronic medical records at X Health Center is not yet fully optimal, namely in the aspects of human, organization and technology.